Determinan Tax Compliance dengan Moral Wajib Pajak UMKM sebagai Variabel Moderasi - Susanto, Freddy; Pituringsih, Endar; Sakti, Dwi Putra Buana (E-Jurnal Akuntansi; Vol 32 No 10 (2022)DO - 10.24843/EJA.2022.v32.i10.p14, 2022)
The purpose of this study is to analyze the effect of tax incentives, tax sanctions on tax compliance where tax morale acts as a moderating variable during the pandemic on MSME taxpayers. The research was conducted in the city of Mataram, West Nusa Tenggara Province. The sampling technique used purposive sampling method with a sample of 100 respondents. Respondents consist of MSME taxpayers or have a turnover of less than 4.8 billion rupiah, be it a business entity or an individual entrepreneur, and take advantage of tax incentives during the pandemic. The data collected is processed using smartPLS 3. The test results found that tax incentives and tax sanctions have an effect on tax compliance. The results of this test are in accordance with attribution theory and justice theory. Where the influence of individual behavior is driven from internal and external where one of them is tax incentives and tax sanctions. However, the study did not find the effect of tax incentives and tax sanctions when moderated by tax morale on tax compliance. Keywords: Tax Incentives; Tax Sanctions; Tax Morals; Tax Compliance